The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1982
DOI: 10.2136/sssaj1982.03615995004600040019x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mycorrhizal Dependency of Troyer Citrange on Glomus fasciculatus in California Citrus Soils and Nursery Mixes

Abstract: In a greenhouse experiment the mycorrhizal fungus, Glomus fasciculatus, significantly increased growth of Troyer citrange (Poncirus trifoliata L.) (TC) seedlings in 20 of 26 methylbromide‐fumigated citrus soils from southern California. Of the six soils in which G. fasciculatus provided no growth increase, two were greenhouse soils, three were nursery soils, and only one was a field soil. Glomus fasciculatus increased foliar P, K, and Cu concentrations and decreased foliar Mg and Na concentrations of TC grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 0 publications
2
29
1
2
Order By: Relevance
“…Menge et al (1982) found that the mycorrhizal dependency of Troyer citrange on G. fasciculatus isolate 0-1 in 26 citrus soils from California was inversely correlated with soil P, Zn, Mn, Cu, percentage organic matter and cation exchange capacity, and was positively correlated with soil pH. In general, arid soils are alkaline in pH, as was the California soil we used (pH 7-3), whereas soils from humid regions, such as Florida, have a pH below 7 (Brady, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menge et al (1982) found that the mycorrhizal dependency of Troyer citrange on G. fasciculatus isolate 0-1 in 26 citrus soils from California was inversely correlated with soil P, Zn, Mn, Cu, percentage organic matter and cation exchange capacity, and was positively correlated with soil pH. In general, arid soils are alkaline in pH, as was the California soil we used (pH 7-3), whereas soils from humid regions, such as Florida, have a pH below 7 (Brady, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…For citrus the magnitude of growth response produced by VAM is referred to as mycorrhizal dependency which is determined in part by the efficiency of the fungus. Mycorrhizal dependency may vary with cultivar, soil factors and mycorrhizal fungus (Menge et al, 1978(Menge et al, , 1982Nemec, 1978). In a test of six citrus cultivars, Nemec (1978) found that differences in efficiency of three Glomus species varied with both rootstock and phosphorus fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that considerable variation exists between mycorrhizal species in their effect on citrus nutrition and growth and between citrus species in their dependence on mycorrhiza (Camprubi & Calvet 1996). of the few published studies on the effect of mycorrhiza on Mg nutrition of citrus, three showed that inoculation with mycorrhiza reduced Mg uptake (Menge 1982;Rocha et al 1995;Souza 2000) and one found an increase (Gendiah & Zaghloul 1997). Melloni & Cordoso (1999) found that the relationship between Mg uptake and the amount of mycorrhizal mycelium on the roots varied depending on the species of citrus grown.…”
Section: Mycorrhizaementioning
confidence: 99%
“…In short, some mycorrhizal fungi may not readily adapt to soils with a pH unlike that of the soil of their origin, thus pH may constrain establishment of arbuscular mycorrhizas. Studies suggesting that this relationship may exist involved the direct liming of soils (Kucey and Diab, 1984;Newbould and Rangeley, 1984), analyses of arbuscular mycorrhizas across diverse soil types (Sylvia et al, 1993b;Menge et al, 1982;Skipper and Smith, 1979), and various management treatments that included fertilizing or physically modifying the soil (e.g. organic amendments, Soedarjo and Habte, 1993).…”
Section: Phmentioning
confidence: 99%